PENGGUNAAN STERANA DAN ISOTOP KARBON UNTUK MENENTUKAN LINGKUNGAN PENGENDAPAN ASAL MATERIAL ORGANIK PADA CEKUNGAN JAWA TIMUR BAGIAN BARAT - Danis Agoes Wiloso (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2017)
Research area is located at western part of Northeast Java Basin there are still many uncertainties concerning aspects of petroleum geochemistry.The oil and the source rock data from wells and seeps were tested according steranes data, and carbon isotope. The oil-oil correlation in the research area has divided the oil samples into two oil groups. The first oil group is the oil group in which the organic material comes from the mix of high plants and algae where the depositional environment of the source rock for this oil group is more headed for shallow marine (deltaic) environment. The second oil group is the oil group in which the organic material comes from more of the high plants where the depositional environment of the source rock for this oil group is more headed for terrestrial environment.